Recording and Analyzing Nucleic Acid Distance Distributions with X‐Ray Scattering Interferometry (XSI). Issue 1 (7th June 2018) - Zettl, Thomas; Das, Rhiju; Harbury, Pehr A. B.; Herschlag, Daniel; Lipfert, Jan; Mathew, Rebecca S.; Shi, Xuesong
Abstract: Most structural techniques provide averaged information or information about a single predominant conformational state. However, biological macromolecules typically function through series of conformations. Therefore, a complete understanding of macromolecular structures requires knowledge of the ensembles that represent probabilities on a conformational free energy landscape. Here we describe an emerging approach, X‐ray scattering interferometry (XSI), a method that provides instantaneous distance distributions for molecules in solution. XSI uses gold nanocrystal labels site‐specifically attached to a macromolecule and measures the scattering interference from pairs of heavy metal labels. The recorded signal can directly be transformed into a distance distribution between the two probes. We describe the underlying concepts, present a detailed protocol for preparing samples and recording XSI data, and provide a custom‐written graphical user interface to facilitate XSI data analysis. © 2018 by John Wiley & Sons, Inc.